TIME MANAGEMENT AS A SHOW OF WORLD VIEW OF MODERN HUMAN - O. Yevtushevska (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
Planning of time always was an inalienable part of social and economic life. However, nowadays time management became so current be-cause of essential changes in society development. Massive production, strict competition, secularization, modern cult of success caused sufficient changes in time perception. Workers, producers, agents, especially in developed countries involved into dynamic economic relations, which demand planning of time and strict daily routine. In our opinion, two main reasons of time management popularity are world-view changes, which make modern secular society radically transforms surroundings of existing and high competition between producers and workers. Time management has its positive advantages, namely it discipline peoples, rise their productivity, reduce wasting of time. However, time management can turn into end in itself.